Ligações de hidrogênio intermoleculares: um estudo teórico da interação entre os heterocíclicos (RC2H4N), R = -H, -OH e -CH3 e ácidos monopróticos HX, COM X = F, CI e CN - Silva Filho, Antonio João da (2014)
This work concerns a theoretical study of structural, electronic, vibrational and topological properties of the R-C2H4NHX hydrogen bonded complexes, where HX (with X = F, Cl and CN) corresponds to proton donors and R-C2H4N proton acceptors are represented by: aziridine (C2H5N), methyl-aziridine (H3C-C2H4N) and hydroxy-aziridine ((HO-C2H4N). Hartree-Fock, DFT (with B3LYP, O3LYP, X3LYP and PBE1PBE hybrid functionals), MP2 and MP4 computational methods were employed with 6-311++G(d,p) Pople s basis set. Quantum Theory of Atoms in Molecules and Natural Bond Orbitals calculations helped in the characterization of the hydrogen bonding between R-C2H4N and HX species. Because to the hydrogen bonded complexes formation the most important changes in structural, electronic and vibrational properties can be highlighted, for example, the HX bond lenght increase; the intermolecular charge transfer from the aziridines to HX species which results, among other effects, in the displacement of the HX stretching band to regions of lower frequency values (red shift effect). The results showed that the HX length bond increment values due to intermolecular interaction followed this trend, regardless of the method used: HX(H3C-AZHX) >HX (AZHX) > HX (HO-AZHX). With respect to the intermolecular energy values, the hydrogen bonded complexes followed the trend: EH3C-AZHF > EAZHF > EHO-AZHF > EH3C-AZHCl > EAZHCl > EHO-AZHCl > EH3C-AZHCN > EAZHCN > EH0-AZHCN. The hydrogen bonded complexes with HF specie, independent of the proton receptor species, have the intermolecular energy values being followed by hydrogen bonded complexes with HCl and HCN. Similarly, the red shift effect values of the HX stretching mode followed the same trend as obtained for the stabilization energy over the range studied. According to the QTAIM criteria the hydrogen bonding was characterized presenting low electron density values in their respective bond critical points, as well as electron density Laplacian positive values. The NBO studies reported the interaction between the free electrons pair present in the nitrogen of the heterocyclics with the antibonding orbital of the proton donor species.